Algorithms in Bioinformatics 11th International Workshop, WABI 2011, Saarbrücken, Germany, September 5-7, 2011, Proceedings - Przytycka, Teresa M.; Sagot, Marie-France (Lecture Notes in Bioinformatics, 2011)
This book constitutes the refereed proceedings of the 11th International Workshop on Algorithms in Bioinformatics, WABI 2011, held in Saarbrücken, Germany, in September 2011. The 30 papers presented were carefully reviewed and selected from 77 submissions. They cover aspects of algorithms in bioinformatics, computational biology and systems biology.